PENYULUHAN KESADARAN LINGKUNGAN KAUM MUDA PERKOTAAN DI KELURAHAN RAPPOCINI KOTA MAKASSAR - K, Syamsu; Nonci, Nurmi; Masdar, Muhammad; Anriani, Haslinda B. (Arunika: Jurnal Pengabdian Masyarakat, 2022)
Environmental problems in urban areas are very concerning. Pollution of accumulated garbage, pollution of vehicles passing by every day, population density affects the quality of ground water that is absorbed, floods that bring dirt into the middle of settlements and so on. Many programs and activities have been attempted to overcome this from the past until now but there have been no significant results. To reduce this, it can be started by raising awareness of young people while cutting generations. Through enlightened youth, they have the potential to move socially in loving the environment so that the urban environment can return to its original nature. Raising awareness among young people is carried out through a literacy movement to groups of environmentalists and youth groups totaling 50 people. They were given material about the importance of the environment and the impact of its damage, especially in the area where they live. They are given training on institutional strengthening and responsibility so that they play a legal role in development. The results of this environmental education indicate the need to increase awareness and knowledge for young people to take the initiative and take a role in protecting the surrounding environment. They were given material about the criteria for a comfortable and uncomfortable environment, then their solutions in overcoming the uncomfortable environment. This initial step should be an example for other communities. The conclusion of this activity is that there needs to be ongoing attention to youth so that they are involved in development through strengthening the role of grassroots institutions such as youth organizations